Usefulness of the Quick-SOFA score in the diagnosis of sepsis in pediatric patients. Servicio Desconcentrado Hospital Pediátrico Dr. Agustín Zubillaga (Boletin Médico de Postgrado, 2020)
The Quick-SOFA score (qSOFA) has not been designed for use in children, although it has been used in numerous studies as a marker of organic dysfunction in sepsis in the absence of a proper score. In order to determine the usefulness of the Quick-SOFA score in the diagnosis of sepsis in pediatric patients who were attended at the Servicio Desconcentrado Hospital Pediátrico Dr. Agustín Zubillaga during the period March-April 2018, a cross-sectional descriptive study was conducted with a total of 60 patients with an average age of 3.03 + 3.76 years of age, predominantly younger infants (40%) as well as male sex (63.3%). The main sites of infection were respiratory (41.6%) and digestive (31.6%). 61.6% of patients had a Glasgow value > 13 points, 68.3% had an elevated respiratory rate and 55% had a systolic blood pressure lower than the percentile for their age. Overall, 75% reported a qSOFA > 2 points and 38.3% presented sepsis. 37.7% of patients with sepsis had a score > 2 and 40% less than 2 points. In this study, qSOFA had a sensitivity of 73.9%, specificity of 24.3%, positive predictive value of 37.78% and negative predictive value of 60%. qSOFA is a simple scale which can facilitate the adequate stratification of risk in pediatric patients with sepsis.
Keywords: sepsis; organ dysfunction scores; pediatrics; infection